A Thomistic Untranslatable: a Conceptual Analysis of Aquinas’ Doctrine of Transubstantiation - Tkachenko, Rostislav (Sententiae, 2016)
The article treats the doctrine of transubstantiation or the Eucharistic change as formulated by Thomas Aquinas in his Summa theologiae, Question 75, against its double conceptual (Christian religious vs. Aristotelian philosophical), as well as double linguistic (Latin vs. translated Greek), background. The doctrine is presented and analyzed as a philosophical-theological theory that can be explicated and assessed using the concept of philosophical untranslatable(s), recently discovered and brought to the fore by the proponents of the “translational turn” in continental philosophy. It is argued on the basis of careful study of Aquinas’ text that the notion of transubstantiation should be identified as a conceptual untranslatable. Here the term “untranslatable” means a unique reinterpretation of Aristotelian language of being and change, which results in a conceptual innovation that has some inherent problems as well as creative and promising inventions. The usage of such a concept is justified by the fact that the reconceptualization that Aquinas did to a number of Peripatetic ideas creates a few untranslatable notions, which do not have much meaning outside the peculiarly Thomistic Latin vocabulary. Despite some criticisms they are not necessarily to be regarded as contradictions, but rather as thomistic untranslatables.